Extraction and evaluation of oleoresin from fresh and dried ginger (Zingiber Officinale Roscoe) - Zamora, Zita G.
This study was designed to develop a laboratory-scale procedure for the extraction of oleoresin from ginger that would give the best yield and quality of the product. In phase I, three extraction times - 3, 5, and 7 hours, and two extracting solvents - alcohol and acetone, were used in determining the combination of time and solvent that would give the best yield and quality of oleoresin. Seven hours alcohol extraction was shown to give the highest yield (22 gms/100 gms dried sample), highest content of fixed oil (13.71 gms/100 gms dried sample), and volatile oil (8.30 gms/100 gms dried sample). However, sensory evaluation showed that the oleoresin from 5 hours alcohol extraction had the best flavor and the highest acceptability when made into a beverage although total yield (17 gms/100 gms dried sample) and fixed oil content (8.64 gms/100 gms dried sample) were lower. In phase II, 7 hours alcohol extraction was used in comparing the oleoresins from fresh and dried ginger as to yield and quality. Fresh ginger was found to give higher yield of oleoresin (39 gms/100 gms dried sample), higher volatile oil content (25.75 gms/100 gms dried sample) but similar fixed oil content (13.25 gms/ 100 gms dried sample) compared to dried ginger. Sensory evaluation however showed no significant differences in the flavor and acceptability of the beverage prepared from the extracts.